LINGUISTIC ANALYSIS OF EMOTIONS IN THE SPEECH PROCESS - Azamova Gulasal Sodiq kizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The linguocognitive model of expressing emotional speech is an approach aimed at studying how a person expresses their emotional state through language tools and the cognitive processes occurring in the brain during this process.